English Medium Instruction: What do we know so far and what do we still need to find out? - Macaro, E (Cambridge University Press, 2022)
English Medium Instruction (EMI), as a phenomenon occurring in the non-Anglophone world, has been matched by a growth in research output on the topic and is now an important and established field of study. A great deal of research attention has been devoted to attitudes held by the key stakeholders in this form of education: teachers, students, and policy makers. Yet, there are many other important questions that remain unanswered, the most important of which are: What are the outcomes of this form of instruction? What is the social and economic impact of EMI? How can EMI teachers improve their teaching? And how can learners help themselves to improve their learning?